Variasi pengobatan malaria rumah tangga di enam provinsi endemis malaria di Indonesia - Mara Ipa; Pandji Wibawa Dhewantara (Loka Litbang Kesehatan Pangandaran, 2015)
Indonesia is targeted to be free of malaria in 2030 and its success is determined by the effectiveness of treatment. Riskesdas 2013 shows the effective treatment of malaria rate as 45.5%. Nationally, only 33.7% of malaria patients received the Artemisinin-based Combination Therapy (ACTs). A further analysis to Riskesdas 2013 data was performed to describe the malaria treatment variation at household-level in six provinces in Indonesia, which are Bengkulu, Maluku, North Maluku, East Nusa Tenggara, Papua, and West Papua. Data of name, type, and sources of drugs, as well as household characteristics was analysed. Total of 287 households that meet the criteria of storing and using drugs for malaria treatment was analysed. The result shows 66 types of drugs with varied sources, including 15 antimalarial drugs (i.e. ACTs, chloroquine, and sulphadoxin-pyrimethamin). Most drugs were obtained from pharmacies and drug shops/ stalls, both in urban and rural areas. Most of the poorest households choose drugstore / stalls (46.7%) for medication. On the other hand, for the wealthier groups, pharmacy is an option to get malaria drugs (48.6%). This research reveals the persistence of resistance from anti-malarial drugs (CQ and SP) in almost all sources, including drugs from official health facilities and health workers. This diverse consumption encourages an effective monitoring, evaluation, and strengthening cross-sector participation to improve knowledge, partnership between community and private sector, and the use of information technology to enhance antimalarial drugs supply management in primary health care. An appropriate form of intervention is substantial to improve the malaria treatment coverage in Indonesia